The glue crisis in surgery of acute aortic dissection type A is ongoing - Karck, Matthias (European journal of cardio-thoracic surgery, 2012)
The story of gelatine-resorcin-formalin (GRF) glue can be dated back as far as 1979, when Guilmet and Bachet described the use of biological glue in acute aorti
Published: 24 November 2012
Gesehen am 26.06.2018